Fragmented populations of leopards in West-Central Africa: facing an uncertain future - (:unkn) unknown (My University, 2013)
During recent decades, most endangered species have suffered serious population declines. Little has been documented on leopards in West-Central Africa and as a result the efficiency of protection measures and wildlife managing practices can be questioned. Using 416 occurrences of leopards, we investigated the relationship between different environmental factors and leopard distribution to establish a baseline distribution of this feline. Leopards are mainly present in two large populations: one in a forest habitat, the other in a savanna habitat. Leopard populations were found to be associated with lions and hyaenas but they avoided human disturbances. Regarding potential breeding dispersal, the Gaussian representation showed a clear fragmentation among populations, suggesting that long-term survival of the species could be threatened. We found no area to be exempt from threats. The leopard has, however, declined less than other carnivore species and still shows viable populations. Furthermore, occurrences were found to be significantly more numerous than expected in protected areas, suggesting the relative efficiency of conservation.
Keywords: African Research